CFD-based calculation method of convective heat transfer coefficient of spiral bevel gear in intermediate gearbox under splash lubrication. Issue 3 (19th January 2021) - Lu, Fengxia; Wang, Meng; Liu, Weizhen; Bao, Heyun; Zhu, Rupeng
Abstract : Purpose: This paper aims to propose a numerical method to calculate the convective heat transfer coefficient of spiral bevel gears under the condition of splash lubrication and to reveal the lubrication and temperature characteristics between the gears and the oil-air two-phase flow. Design/methodology/approach: Based on computational fluid dynamics, the multiple reference frames (MRF) method was used to simulate the rotational characteristics of gears and the motions of their surrounding fluid. The lubrication and temperature characteristics of gears were studied by combining the MRF method with the volume of the fluid multiphase flow model. Findings: The convective heat transfer coefficient can be improved by increasing the rotational speed and the oil immersion depth. Moreover, the temperature of the tooth surface having a large convective heat transfer coefficient is also found to be low. A large convection heat transfer coefficient could lead to a good cooling effect. Originality/value: This method can be used to obtain the convective heat transfer coefficient values at different meshing positions, different radii and different tooth surface positions. It also can provide research methods for improving the cooling effect of gears under the condition of splash lubrication. Peer review: The peer review history for this article is available at: https://publons.com/publon/10.1108/ILT-07-2020-0233/